New aspects of Magellanic cloud research: proceedings of the Second European Meeting on the Magellanic Clouds, held at Heidelberg, Germany, 15 - 17 June 1992 - Baschek, Bodo (Lecture notes in physics, 1993)
The proceedings of the Second European Meeting on "New Aspects of MagellanicCloud Research" review the most recent progress in the study of the LMC and SMC. The activities within the ground-based ESO key programme "Coordinated Investigations of Selected Regions in the Magellanic Clouds", as well as new exciting observations from space missions (ROSAT, IUE, ISO, IRAS) result in a more profound insightinto the structure, kinematics, populations (stars, clusters, interstellar medium), and the chemical composition and evolution of the Magellanic Cloud system. The book addresses researchers and graduate students in astrophysics
Gesehen am 19.11.2015
Keywords: Hochschulschrift; Konferenzschrift; Magellansche Wolken